Moxetumomab pasudotox in relapsed/refractory hairy cell leukemia - Kreitman, Robert; Dietrich, Sascha (Leukemia, 2018)
This is a pivotal, multicenter, open-label study of moxetumomab pasudotox, a recombinant CD22-targeting immunotoxin, in hairy cell leukemia (HCL), a rare B cell malignancy with high CD22 expression. The study enrolled patients with relapsed/refractory HCL who had ≥2 prior systemic therapies, including ≥1 purine nucleoside analog. Patients received moxetumomab pasudotox 40 µg/kg intravenously on days 1, 3, and 5 every 28 days for ≤6 cycles. Blinded independent central review determined disease response and minimal residual disease (MRD) status. Among 80 patients (79% males; median age, 60.0 years), durable complete response (CR) rate was 30%, CR rate was 41%, and objective response rate (CR and partial response) was 75%; 64 patients (80%) achieved hematologic remission. Among complete responders, 27 (85%) achieved MRD negativity by immunohistochemistry. The most frequent adverse events (AEs) were peripheral edema (39%), nausea (35%), fatigue (34%), and headache (33%). Treatment-related serious AEs of hemolytic uremic syndrome (7.5%) and capillary leak syndrome (5%) were reversible and generally manageable with supportive care and treatment discontinuation (6 patients; 7.5%). Moxetumomab pasudotox treatment achieved a high rate of independently assessed durable response and MRD eradication in heavily pretreated patients with HCL, with acceptable tolerability.
Gesehen am 28.10.2019